Efficiency analysis of 67 Chinese research universities considering inter-university heterogeneity: Evidence from a meta-frontier network SBM DEA model - Bo Cheng (PLoS ONE, 2025)
With the continuous increase in technology research and development investment, the overall operational efficiency of universities as the main body of scientific research has always been a focus of research. This study evaluates the efficiency of technology transfer in 67 Chinese universities directly affiliated with the Ministry of Education from 2016 to 2020. By integrating the meta-frontier analysis with the network Slacks-based Measure (SBM) Data Envelopment Analysis (DEA) approach, we assess the overall efficiency, stage-specific efficiency, and sources of inefficiency across different types of universities. Results indicate that while some institutions operate at the optimal frontier, the overall efficiency remains moderate, with the Technology Transfer and Application (TTA) stage consistently underperforming compared to the R&D stage. Significant heterogeneity exists among university types: normal, and medical & pharmaceutical universities demonstrate higher efficiency levels, whereas comprehensive, science and engineering, and agricultural and forestry universities exhibit notable inefficiencies, particularly in the TTA stage. Further decomposition reveals that technological gaps are the dominant source of inefficiency, especially in the later stage of the innovation process. Based on these findings, we propose targeted policy recommendations aimed at improving infrastructure, enhancing management practices, and tailoring reform strategies according to institutional type. This study contributes to the understanding of internal inefficiencies in university-led technology transfer and provides practical insights for policymakers and university administrators seeking to enhance the commercialization of academic research.